(untitled) (Nepal Journal of Environmental Science, 2024)
This paper has aimed to concisely discuss the insight into the potential of the Argeli bast fibers as reinforcing agents in eco-friendly polymer composites. The Argeli fibers used in this work as biofiller were prepared by mechanical disintegration of the sun-dried Argeli bast fiber bundles followed by chemical treatments and hence incorporated into the matrix of the PLA/PBAT blend via melt compounding. The materials were characterized by advanced analytical tools such as tensile and Shore D hardness testing, and optical and electron microscopy. The Argeli fibers, originally comprising the compact bundles of microfibrils glued together, were found to exfoliate into constituent microfibers and distribute uniformly in the PLA/PBAT blends matrix upon melt processing. The addition of Argeli fiber into the PLA/PBAT mixture led to a reinforcement of the polymeric matrix with an increase in the tensile modulus as well as Shore D hardness, the properties being further enhanced with chemical treatments of the fibers. The latter enhancement in properties was attributed to the chemical treatment-induced formation of a highly crystalline pure cellulosic framework due to the dissolution of the amorphous parts as well as other impurities from the neat fibers. The Argeli fibers exhibited a potential reinforcing agent for the biodegradable polymer composite.